Molecular analysis of SNF2 and SNF5, genes required for expression of glucose-repressible genes in Saccharomyces cerevisiae. - Abrams, E (1986)
The SNF2 and SNF5 genes are required for derepression of SUC2 and other glucose-repressible genes of Saccharomyces cerevisiae in response to glucose deprivation. Previous genetic evidence suggested that SNF2 and SNF5 have functionally related roles. We cloned both genes by complementation and showed that the cloned DNA was tightly linked to the corresponding chromosomal locus. Both genes in multiple copy complemented only the cognate snf mutation. The SNF2 gene encodes a 5.7-kilobase RNA, and the SNF5 gene encodes a 3-kilobase RNA. Both RNAs contained poly(A) and were present in low abundance. Neither was regulated by glucose repression, and the level of SNF2 RNA was not dependent on SNF5 function or vice versa. Disruption of either gene at its chromosomal locus still allowed low-level derepression of secreted invertase activity, suggesting that these genes are required for high-level expression but are not directly involved in regulation. Further evidence was the finding that snf2 and snf5 mutants failed to derepress acid phosphatase, which is not regulated by glucose repression. The SNF2 and SNF5 functions were required for derepression of SUC2 mRNA.